Antidiarrhoeal Activity of Methanolic Stem Bark Extract of Sarcocephalus latifolius in Castor Oil-Induced Diarrhoeal Albino Rats - Ahmed, Maryam Usman; Titus, Diowato; Isa, Ruqayya (Darul Yasin Al Sys, 2024)
Diarrhoea remains one of the leading causes of death among children in developing countries characterized by frequent passing of watery faeces. This study eval_uates the antidiarrhoeal activities of Sarcocephalus latifolius in castor oil-induced diarrhoeal albino rats. Thirty (30) albino rats were divided into six groups of five rats each. Except group 1 (control group) which received distilled water, all groups received 0.5 mL castor oil to induce diarrhoea. Group 2 received loperamide 3 mg/kg b. wt. Group 3, 4, 5, and 6 received 100, 200, 300, and 400 mg/kg b. wt. respectively of the methanolic stem bark extract of Sarcocephalus latifolius. Total diarrhoeic faeces, stool inhibition, intestinal fluid accumulation, and intestinal transit was determined to eval_uate the antidiarrhoeal effect of the extract. Total diarrhoeal faeces, intestinal content and intestinal transit reflects significant (p<0.05) decrease with increase in the dose of the extract, group 4 which received high dose (400 mg/kg b. wt.) shows no significant difference when compared with group 2 which received loperamide. Percentage inhibition increases with increase in dose. Methanolic stem bark extract of S. latifolius possess antidiarrhoeal effect on castor oil-induced diarrhoea.